Birth outcomes following antiretroviral exposure during pregnancy: Initial results from a pregnancy exposure registry in South Africa - Ushma C. Mehta; Cari van Schalkwyk; Prineetha Naidoo; Arthi Ramkissoon; Otty Mhlongo; Niren R. Maharaj; Niree Naidoo; Karen Fieggen; Michael F. Urban; Shaun Krog; Alex Welte; Mukesh Dheda; et al. (Southern African Journal of HIV Medicine, 2019)
Background: In 2013, a pregnancy exposure registry and birth defects surveillance (PER/BDS) system was initiated in eThekwini District, KwaZulu-Natal (KZN), to assess the impact of antiretroviral treatment (ART) on birth outcomes.